2023
DOI: 10.3390/brainsci13121619
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological and Psychometric Outcomes in Minimal Consciousness State after Advanced Audio–Video Emotional Stimulation: A Retrospective Study

Rosaria De Luca,
Paola Lauria,
Mirjam Bonanno
et al.

Abstract: In the last ten years, technological innovations have led to the development of new, advanced sensory stimulation (SS) tools, such as PC-based rehabilitative programs or virtual reality training. These are meant to stimulate residual cognitive abilities and, at the same time, assess cognition and awareness, also in patients with a minimally conscious state (MCS). Our purpose was to evaluate the clinical and neurophysiological effects of multi-sensory and emotional stimulation provided by Neurowave in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…The Group X Phase interaction emphasized that these differences were influenced by the type of intervention (Erigo vs. Control), highlighting the specific impact of each intervention on cognitive functioning and overall functional independence in MCS patients. These results are in line with our previous study, in which we found that RVT alone or plus music stimulation [15] improved the overall cognitive functioning, tested with LCF. Frazzitta et al (2016) [46] found that patients with DoC improved their global functioning tested with Coma recovery scale (CSR-r) after RVT with Erigo, although scores in LCF at post-treatment were not significant.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The Group X Phase interaction emphasized that these differences were influenced by the type of intervention (Erigo vs. Control), highlighting the specific impact of each intervention on cognitive functioning and overall functional independence in MCS patients. These results are in line with our previous study, in which we found that RVT alone or plus music stimulation [15] improved the overall cognitive functioning, tested with LCF. Frazzitta et al (2016) [46] found that patients with DoC improved their global functioning tested with Coma recovery scale (CSR-r) after RVT with Erigo, although scores in LCF at post-treatment were not significant.…”
Section: Discussionsupporting
confidence: 93%
“…In this context, among the non-pharmacological therapies, early intensive neurorehabilitation combining physical, occupational, speech, and neuropsychological therapy appears to improve long-term functional recovery [12][13][14][15][16]. Specialized rehabilitation protocols for DoC individuals are essential for improving recovery and long-term care.…”
Section: Introductionmentioning
confidence: 99%
“…Many children with CP experience rigidity or weakness in muscles that tends inevitably towards fixed or irreversible deformities. The impairment of muscle activation and motor control has a negative impact on the performance of daily activities such as dressing, feeding, and playing, as well as on cognition [6]. Currently, CP stands as the leading cause of childhood disability.…”
Section: Introductionmentioning
confidence: 99%